A Multicenter Study: North American Islet Donor Score in Donor Pancreas Selection for Human Islet Isolation for Transplantation. Issue 8 (August 2016) - Wang, Ling-Jia; Kin, Tatsuya; O'gorman, Doug; Shapiro, A. M. James; Naziruddin, Bashoo; Takita, Morihito; Levy, Marlon F.; Posselt, Andrew M.; Szot, Gregory L.; Savari, Omid; Barbaro, Barbara; McGarrigle, James; et al.
Selection of an optimal donor pancreas is the first key task for successful islet isolation. We conducted a retrospective multicenter study in 11 centers in North America to develop an islet donor scoring system using donor variables. The data set consisting of 1, 056 deceased donors was used for development of a scoring system to predict islet isolation success (defined as postpurification islet yield >400, 000 islet equivalents). With the aid of univariate logistic regression analyses, we developed the North American Islet Donor Score (NAIDS) ranging from 0 to 100 points. The c index in the development cohort was 0.73 (95% confidence interval 0.70–0.76). The success rate increased proportionally as the NAIDS increased, from 6.8% success in the NAIDS < 50 points to 53.7% success in the NAIDS ≥ 80 points. We further validated the NAIDS using a separate set of data consisting of 179 islet isolations. A comparable outcome of the NAIDS was observed in the validation cohort. The NAIDS may be a useful tool for donor pancreas selection in clinical practice. Apart from its utility in clinical decision making, the NAIDS may also be used in a research setting as a standardized measurement of pancreas quality.